PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA KARTU GAMBAR TERHADAP HASIL BELAJAR SISWA KELAS lV SD NEGERI SEPANDE - Indriyanty Novi; Setiyawati Enik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an essential part of the educational process in elementary schools because it plays a significant role in shaping students’ attitudes, values, and behaviors in their daily lives. This research seeks to examine the role of teachers in implementing character education among students at SD Negeri Sepande.The research uses a quantitative approach with a Pretest-Posttest Control Group Design. The population of the study consists of all fourth-grade students in an elementary school, and the sampling technique applied is random sampling. The research instrument used is a science (IPA) learning achievement test. Data analysis is conducted through normality testing, homogeneity testing, and an independent t-test to determine the differences in learning outcomes between the experimental class and the control class. The results of the study indicate that the implementation of the cooperative learning model type Make a Match assisted by picture card media has a positive and significant effect on elementary school students’ science learning outcomes. This is evident from the increase in the average learning outcome scores of the experimental class compared to the control class. Therefore, it can be concluded that the Make a Match model is effective in science learning to enhance students’ activeness and learning outcomes at the elementary school level.